2002
DOI: 10.1603/0022-2585-39.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Northern Distribution of <I>Aedes albopictus</I> (Diptera: Culicidae) in Japan by Geographical Information System

Abstract: Aedes albopictus (Skuse), a mosquito vector of the dengue fever virus, is prevalent in Japan, distributed widely in Honshu Island with its northern limits between latitude 38 degrees to 40 degrees north. The factors affecting distribution of the species in the northern part of Japan were studied using the geographical information system (GIS). During 1998-2000, larval surveillance was carried out in 26 urban and rural areas in the Tohoku district, in the northern part of Honshu Island, by collecting larvae fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
179
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(190 citation statements)
references
References 9 publications
7
179
2
2
Order By: Relevance
“…A critical daylight threshold of 13 to 14 hours was reported in strains of Aedes albopictus from Shanghai and Nagasaki (Wang 1966, Mori et al 1981, North America (Pumpuni et al 1992), and Italy (Toma et al 2003). In another Nagasaki study, a critical photoperiod of 11 to 12 hours was reported (Kobayashi et al 2002). In Italy, some eggs were able to hatch with a day length of 10 hours (Toma et al 2003).…”
Section: Input Parametersmentioning
confidence: 98%
See 4 more Smart Citations
“…A critical daylight threshold of 13 to 14 hours was reported in strains of Aedes albopictus from Shanghai and Nagasaki (Wang 1966, Mori et al 1981, North America (Pumpuni et al 1992), and Italy (Toma et al 2003). In another Nagasaki study, a critical photoperiod of 11 to 12 hours was reported (Kobayashi et al 2002). In Italy, some eggs were able to hatch with a day length of 10 hours (Toma et al 2003).…”
Section: Input Parametersmentioning
confidence: 98%
“…The daily records were transformed into the number of days with temperatures higher than 11° C (Kobayashi et al, 2002). First, the total number of days with temperatures exceeding the threshold was calculated, and then the degree days were calculated by summing up the temperature and subtracting the threshold of those days.…”
Section: Temperature and Rainfallmentioning
confidence: 99%
See 3 more Smart Citations